Experience in local Glyciphon chemotherapy of basal cell carcinoma of the problem face areas - S. O. Podvyaznikov (Опухоли головы и шеи)
Basal cell carcinoma (BCC) is the most common type of malignant skin tumors, characterized by selective localization on the head and neck. Currently there is a variety of treatment methods for this disease, but some of them are not feasible due to patients’ age, cancer localization, morphological type, size, or number of tumor lesions. In that respect, local chemotherapy of BCC, especially for the problem face areas, can serve as a good alternative. Clinical and experimental trials have shown a high treatment effect for 30 % Glyciphon ointment in patients with BCC. In this article we present successful examples of treatment of patients with BCC on the problem face areas using Glyciphon.